DISTRAKSI SEBAGAI SALAH SATU PENDEKATAN YANG DILAKUKAN DALAM MENCAPAI KEBERHASILAN PERAWATAN GIGI ANAK: DISTRACTION TECHNIQUE AS AN APPROACH TO ACHIEVE A SUCCESS IN DENTAL CHILD TREATMENT - Soesilo Soeparmin (TALENTA, 2010)
The important thing of success in dental treatment for children is reducing fear and anxiety. It can prevent traumatic feeling and relaxant to the treatment. Distraction technique is a process of shifting in focus attention from pain to the other stimulus, so it is used to the child’s focus attention in order to avoid a pain. There are several distraction techniques, such as visual, hearing, resparation, intelectual and guidance imagination distraction. All types of music can be used in decreasing children’s anxiety actually, a therefore it is important to facilitate music in dental private practise. As conclusion, hearing distraction with music is a very simple distraction technique, easy and very effective in decreasing patient anxiety, before and during the dental treatment. Music can help patient to feel convenience before and during the dental treatment.